Reading Partnership between Challenged and Knowledgeable (Repack) Read-ers to Improve Performance: PROJECT REPACK - Enriquez, Rinalyn D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Reading has been capitalized in the education process. It has been put premium in the context of the learning recovery as the return of in-person of classes is observed. This action research aimed to examine the reading performance level of Grade One pupils of Camiing Elementary School before and after the employment of project RePACK (Reading Partnership between Challenged and Knowledgeable). This study further determined the aspects of the introduced intervention that facilitated their reading performance. The participants of the study were the 45 Grade one pupils of Camiing Elementary School School of Schools Division of Zambales in the school year 2022-2023. The data were gathered through a mixed method. The qualitative part employed thematic analysis to interpret the transcribed interviews. On the other hand, the quantitative one-group pretest-post-test design used the mean and paired sample t-test to measure the reading performance of the learners in the phases of treatment. The analysis of how the project RePACK facilitate their reading performance has emerged into two themes: availability of learning support, and access to reading resources. The level of learners’ oral word recognition in the pre-intervention was found frustration and instructional in the post-intervention. Similarly, there was a leaped in progression of the reading comprehension of the leaners where they were marked frustration in the pre-test and independent in the post-test. Notably, there is a significant difference in the learners’ reading performance level before and after the intervention. This outcome suggests that the project RePACK is effective in improving the reading performance of the learners. In this regard, school heads, teachers, and students are encouraged to adopt the intervention because of its efficacy.